Postpartum health of working mothers: A prospective study - Majorie Ensayan Anak Janting; Whye Lian Cheah; Helmy Hazmi (Malaysian Family Physician, 2023)
Introduction: Most working women experience poor physical and mental health during their postpartum period. This prospective study aimed to describe the physical and mental health issues faced by working mothers during their postpartum period. Methods: Respondents were recruited using the proportional sampling method among mothers who attended the Maternal and Child Health Clinic in the Kuching division in Sarawak, Malaysia. Face-to-face interview was conducted using a questionnaire that consisted of items on socio-demographic data as well as perinatal, prenatal and postpartum factors, and the Edinburgh Postnatal Depression Scale and a checklist of 28 specific postpartum symptoms were used during the first 6 weeks and after 12 weeks of childbirth. Results: A total of 281 respondents participated in this study. Fatigue (42.7%), back or neck pain (36.3%), breast discomfort (16.4%), dizziness (13.5%) and nipple irritation (11.0%) were among the most common symptoms experienced by the mothers during the first 6 weeks after childbirth. There was a significant decrease in the physical symptom scores of the respondents from the first 6 weeks to after 12 weeks of childbirth (1.73±1.96 vs 0.16±0.42; P<0.0005). A significant decrease was also found in the depression scores (6.26±4.26 vs 1.35±1.85, P<0.0005). Conclusion: The prevalence of postnatal depression was higher during the first 6 weeks of postpartum than after 12 weeks of postpartum. Screening and treatment of poor postpartum mental health among working women are essential owing to the impacts on occupational outcomes.